Gynecologic Cancer InterGroup (GCIG) Consensus Review for Cervical Adenocarcinoma. (1st November 2014) - Fujiwara, Hiroyuki; Yokota, Harushige; Monk, Bradley; Treilleux, Isabelle; Devouassoux-Shisheboran, Mojgan; Davis, Alison; Kim, Jae-Weon; Mahner, Sven; Stany, Michael; Pignata, Sandro; Ray-Coquard, Isabelle; Fujiwara, Keiichi
Abstract : Cervical adenocarcinoma is known to be less common than squamous cell carcinoma of the cervix comprising approximately 25% of all cervical carcinomas. Differences in associated human papillomavirus types, patterns of spread, and prognosis call for treatments that are not always like those for squamous cancers. In this review, we report a consensus developed by the Gynecologic Cancer InterGroup surrounding cervical adenocarcinoma for epidemiology, pathology, treatment, and unanswered questions. Prospective clinical trials are needed to help develop treatment guidelines. Key points: Differences between adenocarcinoma and squamous cell carcinoma, and Individualization of the therapy